2008
DOI: 10.1038/ajh.2007.77
|View full text |Cite
|
Sign up to set email alerts
|

Association of Microalbuminuria With Brachial-Ankle Pulse Wave Velocity: The Ohasama Study

Abstract: Microalbuminuria appears to be associated with baPWV more closely than with IMT and ABP, and its association with baPWV is independent of ABP and other cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 29 publications
8
43
0
Order By: Relevance
“…In addition, there was a significant correlation between urinary protein excretion and baPWV. Recent studies have shown urinary protein excretion to be more closely associated with baPWV than with ambulatory BP level, 40 and that baPWV increased with a decrease in renal function or with proteinuria independently of other risk factors, 41 thereby supporting the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, there was a significant correlation between urinary protein excretion and baPWV. Recent studies have shown urinary protein excretion to be more closely associated with baPWV than with ambulatory BP level, 40 and that baPWV increased with a decrease in renal function or with proteinuria independently of other risk factors, 41 thereby supporting the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…Comparisons have often examined the issues of whether ambulatory, office, day or night time BPs were similar determinants of nephropathies. [24][25][26][27] Few studies have directly compared different BP variables from the same measurements for the prediction of nephropathy, including in people with diabetes. These studies have generally emphasized the importance of SBP over DBP in promoting the development and progression of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…15 --18 Microalbuminuria is associated with increased baPWV in the general population, 16 and an increase in baPWV predicts the development of microalbuminuria in patients with hypertension. 18 The present findings are consistent with these previous studies and have extended them to a population with normal albuminuria.…”
Section: Discussionmentioning
confidence: 99%